The Effect of Empowerment, Development, Welfare and Community Participation on Village Fund Allocation - Aditya, Ramanda Eka; Hendra Ts, Kartika; Pawenang, Supawi (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to test and analyze the influence of empowerment, development, welfare, community participation on village fund allocation. This research method uses quantitative research design. The population used in this study is the community of Medungsari Village, Gondangrejo District with a total of 3,120 people. Sampling using purposive sampling technique obtained 100 respondents Data collection using questionnaires. The data analysis technique used statistical analysis, namely multiple linear regression test, F test, t test, and coefficient of determination. The results of the study indicate that empowerment, development, welfare, community participation partially and simultaneously have a positive and significant effect on village fund allocation (ADD) in Mendungsari Village, Bulurejo, Gondangrejo, Karanganyar Suggestions from this study, always increase empowerment, development, welfare, and community participation, so that it can increase village fund allocation (ADD).